2016
DOI: 10.1044/2016_aja-15-0059
|View full text |Cite
|
Sign up to set email alerts
|

Revised Conceptual Framework of Parent-to-Parent Support for Parents of Children Who Are Deaf or Hard of Hearing: A Modified Delphi Study

Abstract: The findings from this dual-stage scoping review and electronic Delphi study provide a conceptual framework that defines the vital contribution of parents in Early Hearing Detection and Intervention programs that will be a useful addition to these programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In contrast, our study aimed to elicit KM factors most relevant to key stakeholder groups through agreement and consensus building by experts. The consensus building focus is one of the key strong points of Delphi studies (Henderson et al, 2016). Similarly, traditional quantitative surveys are limited in gathering iterative feedback and seeking consensus, and therefore not suited for our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our study aimed to elicit KM factors most relevant to key stakeholder groups through agreement and consensus building by experts. The consensus building focus is one of the key strong points of Delphi studies (Henderson et al, 2016). Similarly, traditional quantitative surveys are limited in gathering iterative feedback and seeking consensus, and therefore not suited for our study.…”
Section: Methodsmentioning
confidence: 99%
“…The Delphi study approach has been used in many comparable study settings (Bagheri et al, 2017; Fletcher & Marchildon, 2014; Henderson et al, 2016). Compared to other approaches such as grounded theory, phenomenology, constructivist inquiry, narrative inquiry, and surveys, the Delphi method is low cost, easy to use, enables access to a sample of geographically dispersed experts, emphasizes consensus building, and provide a pragmatic way to develop theories and models that are testable in subsequent studies (Brady, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, there are currently no validated tools that could measure these types of Environmental outcomes associated with speech-language pathology interventions. The development of a field-specific quantitative measure may be an important future research direction, given that group and professional supports have been identified as important in multiple studies on MTW (Denusik et al, 2023; Garnett et al, 2022b; Patterson & Smith, 2011 ) as well as more generally in research on providing child- and family-centered care ( Henderson et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The families in this study, all of whom participated in family-centered EI, articulated a sense of empowerment and advocacy in a variety of instances ranging from fighting for funding for their child’s hearing equipment to making sure they had access to their desired center-based program. Similar to Henderson et al (2016), the parents who participated in this study also involved themselves in informal networks (e.g., joining Facebook groups, and connecting with families in their religious communities) that extended their information gathering beyond their formal EI sessions at the center. This highlights the importance of community-building and community-extending, both within the family-centered EI program and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…The opportunity to build relationships among families with children at similar stages of development is a central tenet of EI, particularly when it takes place in group settings, such as center-based programs. Parents who participate in both formal support groups and informal networking with other parents of DHH children often report a feeling of empowerment beyond that provided during individual EI sessions (Henderson et al, 2016). Connections to other parents may provide families with assistance in navigating EI systems, transitioning between EI and preschool services, and advocating for high-quality EI providers.…”
Section: Family-centered Early Interventionmentioning
confidence: 99%